Digital Competencies for Pla and Plac Teachers: A Path with No Shortcuts or Returns - Dos Santos-Marques, A (UNESP-FACULDADE CIENCIAS & LETRAS, 2021)
The aim of this article is to examine the increase in digital competencies of PLA and PLAc teachers for their performance in the context of virtual teaching. Our interest arises from the challenges that this modality imposes on the classes due to the Sars-CoV-2 virus pandemic. We develop our proposal by reviewing studies of teaching areas in virtual environments and the teaching of foreign languages. Our methodological design considers the configuration of a case study, in a qualitative approach to the data tointerpret our object of study. The results point to how teachers face the pressures about their digital skills to respond to the immediate needs of their contexts. Also, they recognize a great dependence on digital literacy for their professional performance and for the training of their students, offering them opportunities to participate both in educational and social scopes in Portuguese.